Evaluation and Comparison of the Morphological Dimension of Mandibular Symphysis in Skeletal Class i and Class ii Individuals with Different Growth Patterns: A Cephalometric Study - Akhare, Pankaj; Rajagopal, Akshaya; Shenoy, Usha; Banerjee, Sujoy; Hazarey, Ananya; Karia, Himija; Bhattacharya, Sangeeta (International Journal For Research In Health Sciences And Nursing, 2018)
Mandibular symphysis is an anatomical structure of the mandible in which the lower incisors and the anterior portion of the chin are found. It is morphologically divided into two regions, the dentoalveolar and basal symphyses.1The dentoalveolar symphysis consists of alveolar process and lower incisors. Alveolar bone thickness varies according to location and facial type.2 Generally, there is a greater bone thickness at the apex then in the cervical region and towards the lingual surface when compared to the labial surface.2 The lingual side of cortical bone is thicker than the buccal and there is a closer approximation of the root apex to the lingual cortical. The basal symphysis is a part of the main body of the mandibular symphysis with more apical location. The morphological variation of the menton has a strong genetic basis.